Depth-dose distribution in potatoes with low-energy X-rays - Nguyen, Thi Nguyet Ha; Tamikazu, Kume; Nguyen, An Son; Nguyen, Thi Minh Sang; Pham, Thi Ngoc Ha; Nguyen, Danh Hung; Cao, Van Hai; Nguyen, Quang Kien; Nguyen, Huu Duc; Do, Thi Le (Hue University Journal of Science: Natural Science, 2022)
Irradiation is known as a handful measure to inhibit potato sprouting, kill harmful bacteria, and increase preservation. The absorbed dose is one of the essential characteristics of the irradiation process. In this study, the depth-dose distributions in potatoes and polymethyl methacrylate were investigated under low-energy X-ray irradiation by using the Fricke dosimeter and Gafchromic film dosimeter. The dose rates required for the rays to penetrate in polymethyl methacrylate were compared with those in potatoes. Polymethyl methacrylate could be used as a phantom in measuring the depth dose delivered in potatoes. The difference in depth-dose distribution in potatoes between one-sided and double-sided irradiation was also investigated. The calculated dose uniformity ratio values are 5.8 and 1.9 for potatoes irradiating one-sided and double-sided.